Probiotics in the Management of Lung Diseases - Esmaeil Mortaz; Ian M. Adcock; Gert Folkerts; Peter J. Barnes; Arjan Paul Vos; Johan Garssen (Hindawi Limited, 2013)
The physiology and pathology of the respiratory and gastrointestinal tracts are closely related. This similarity between the two organs may underlie why dysfunction in one organ may induce illness in the other. For example, smoking is a major risk factor for COPD and IBD and increases the risk of developing Crohn's disease. Probiotics have been defined as "live microorganisms which, when administered in adequate amounts, confer health benefits on the host." In model systems probiotics regulate innate and inflammatory immune responses. Commonly used probiotics include lactic acid bacteria, particularly Lactobacillus, Bifidobacterium, and Saccharomyces, and these are often used as dietary supplements to provide a health benefit in gastrointestinal diseases including infections, inflammatory bowel disease, and colon cancer. In this respect, probiotics probably act as immunomodulatory agents and activators of host defence pathways which suggest that they could influence disease severity and incidence at sites distal to the gut. There is increasing evidence that orally delivered probiotics are able to regulate immune responses in the respiratory system. This review provides an overview of the possible role of probiotics and their mechanisms of action in the prevention and treatment of respiratory diseases.